Lower self-positivity and its association with self-esteem in women with borderline personality disorder - Winter, Dorina; Schmahl, Christian; Bohus, Martin; Lis, Stefanie (Behaviour research and therapy, 2018)
Self-esteem, the global attitude towards one's self, is low in persons with borderline personality disorder (BPD). This may be partially due to the ways these persons protect or enhance the self. A case in point is self-positivity, the association of positive rather than negative events, experiences, and objects with the self. Self-esteem and self-positivity may result from either conscious or non-conscious processes. We examined whether low self-esteem is related to low self-positivity in BPD, and whether their covariation is contingent upon conscious processing. We assessed explicit self-esteem via self-report (Rosenberg Self-Esteem Scale) and implicit self-esteem via the Initial Preference Task in women with BPD and healthy control women. We assessed self-positivity in a self-referential processing task, in which participants rated the valence of positive, neutral, and negative nouns, and later recalled them. We manipulated referential context via supraliminal or subliminal priming of self-reference, other-reference, or no reference. Explicit and implicit self-esteem were lower in the BPD group than in the healthy control group. Participants with BPD rated self-referential words less positively, when primes were presented supraliminally. Less positive and slower ratings of positive self-referential words were associated with lower explicit, but not implicit, self-esteem in the BPD group.
Gesehen am 31.03.2020